Finite aﬃne algebras are fully dualizable. Issue 4 (3rd April 2018) - Bentz, Wolfram; Gillibert, Pierre; Sequeira, Luís
ABSTRACT: We show that every finite aﬃne algebra A admits a full duality. In the process, we prove that A also allows a strong duality, and that the duality may be induced by a dualizing structureA ∼ of finite type. We give an explicit bound on the arities of the partial and total operations appearing inA ∼ . In addition, we show that the enriched partial hom-clone of A is finitely generated as a clone.